Determination of species of white grubs (Coleóptera: Scarabaeidae) present in grassland plots, weeping lovegrass and cultivated lands of the province of San Luis (Semiárida, 2020)
The larvae of Coleoptera Scarabaeidae are members of the edaphic fauna. Their populations benefit from techniques such as no-till farming: the population increase is associated with the increase of cover and absence of tillage, among other aspects. Within the group of “white grubs”, the big family Scarabaeidae is found. Most of them are phytophagous and harmful to agriculture. These larvae live in lands of The Pampas (Argentine lowlands) and belong to different species. The Group of “white grubs” is one the groups most recognized for not disrupting the habitat. This is why the net rate of growth of its populations is supposed to increase throughout the years. The lack of studies on the diversity of “white grubs” (Coleoptera:Scarabaeidae), in the natural grassland of the province of San Luis, motivated this study, which provides a basis for the integrated management of the different systems of production of the area. In any of these three conditions, the constant presence of Cyclocephala putrida is observed.
Keywords: Grassland; Scarabaeidae; Diversity